Initial experience of sleeve lobectomy under complete video‐assisted thoracic surgery. Issue 1 (29th November 2017) - Ma, Shaohua; Yan, Tianshen; Liu, Dandan; Wang, Keyi; Wang, Jingdi; Song, Jintao; Wang, Tong; He, Wei; Bai, Jie; Jin, Liang; Liang, Hailong
Abstract: Purpose: Review the initial results of a single‐center complete video‐assisted thoracoscopic surgery (VATS) sleeve lobectomy and discuss the key procedure of this operation, in addition to its safety and feasibility. Methods: Retrospectively analyze the perioperative data of 11 patients who accepted complete VATS sleeve lobectomy between May 2013 and Jun 2017 in Peking University Third Hospital, try to evaluate the safety of this procedure. All the patients were followed up and their oncological recurrence and metastasis were observed, and feasibility of VATS sleeve lobectomy for lung cancer was evaluated. Results: All of the 11 cases underwent complete VATS sleeve lobectomy successfully and there is no conversion to thoracotomy. The mean operative time was 338 min (range from 243 to 511 min), the mean time of bronchial anastomotic was 63 min (range from 40 to 96 min), the mean blood loss was 205 mL (range from 50 to 400 mL), and the mean number of lymph nodes dissected is 22.1. There was no other complication except one patient suffered from high‐risk pulmonary embolism, and no anastomotic leakage and stricture was found. The mean hospital stay postoperation was 8.7 days. The time of follow‐up was between 2 and 38 months, only one out of the 11 cases died of bone metastasis, and the other 10 survived till now. One of these 10 patients had local recurrence 24 months after operation, and one suffered adenocarcinoma of esophageal–gastric junction at 15 months postoperation. The rest of eight patients all survived to June 2017 and no local recurrence and metastasis was found. The mean survival time was 14.8 months. Conclusion: Complete VATS sleeve lobectomy is a safe and feasible procedure, but the advantage of perioperative and long‐term survival need prospective randomized controlled large sample trial to be confirmed.